2005
DOI: 10.1108/17422040510595645
|View full text |Cite
|
Sign up to set email alerts
|

The networked union? The internet as a challenge to trade union identity and roles

Abstract: PurposeThe article aims to look at the development of the internet in terms of its implications for the labour movement and its international activities.Design/methodology/approachThe paper brings together conclusions and findings based on the previous work of the two individual authors who have studied the role of the internet from a national and international perspective, using a range of methodologies.FindingsThe impact of the internet in terms of facilitating communication and renewal strategies has been h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 30 publications
1
46
1
Order By: Relevance
“…In contrast to this, other writers were less optimistic, citing the need to avoid the binary contrast between ‘bureaucracy’ and the ‘Internet’ (Martinez Lucio, : 338), calling for a more nuanced understanding of union communications online (Martinez Lucio and Walker, ; Martinez Lucio et al , ). This requires acknowledgement of the political dimension of unionism as ‘as well as opening up new communication spaces, the Internet can be used by pre‐existing technological and organisational elites both within and beyond leadership structures to close down or restrict discussions’ (Martinez Lucio et al , : 117).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this, other writers were less optimistic, citing the need to avoid the binary contrast between ‘bureaucracy’ and the ‘Internet’ (Martinez Lucio, : 338), calling for a more nuanced understanding of union communications online (Martinez Lucio and Walker, ; Martinez Lucio et al , ). This requires acknowledgement of the political dimension of unionism as ‘as well as opening up new communication spaces, the Internet can be used by pre‐existing technological and organisational elites both within and beyond leadership structures to close down or restrict discussions’ (Martinez Lucio et al , : 117).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A complex relationship exists between young workers and unions, with the extant literature, suggesting that while young workers are not against unionisation, membership among this age group is particularly low (Hodder and Kretsos, ). Much has been written about the potential for unions to embrace the Internet (Greene et al , ; Martinez Lucio and Walker, ) and social media platforms such as Facebook, Twitter and YouTube (Bryson et al , ; Panogiotopolus and Barnett, ) to engage young workers and improve levels of organisation and activism. It has been suggested that these new technologies are ‘changing the face of community engagement because of their ability to recruit people to causes, organize collective action, raise awareness, influence attitudes, raise funds, and communicate with decision‐makers’ (McAllister, : 93).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of collective workplace action and solidarity, we must assess the ability of web based communication to transcend not just the content but more importantly the form of power and authority in trade unions (Martinez Lucio, 2003;Martinez Lucio and Walker, 2005). In a recent review of trade union use of the internet more generally, Richards (2010: 10) concludes that trade union members are 'more intense users of ICTs than their nonunionised counterparts'.…”
Section: Distributed Discourse -A Weapon For or Against The Union?mentioning
confidence: 99%
“…Much has been written on trade union use of the web, either as a tool for organising or as a vehicle by which existing power relations (such as employer and union leaderships) can be challenged (Hogan and Greene, 2002;Cockfield, 2005: Martinez Lucio and Walker, 2005: Mosco, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Yet, irrespective of official views of the Internet and their link with labour (such as Lee's) and more activist‐oriented approaches such as Greene and Hogan, unions have advanced greatly in their ability to engage with the Internet and create centrally controlled spaces for intra‐ and extra‐union communications. The Internet and its impact are in part mediated by trade union traditions, structures and identity (Martínez Lucio, 2003; Martínez Lucio and Walker, 2005). The significance of this argument is that the Internet is mediated and used in a variety of ways.…”
Section: Trade Unions the Internet And Polish Migrant Workers: The Lmentioning
confidence: 99%